Spain and the European Union: topical issues of interaction - Natalia Sharoichenko (Ибероамериканские тетради, 2017)
This article analyzes various aspects of interaction of Spain and European Union (EU) at the present stage. Due to the fact that the studied period is less than six months (including several events happened in a period less than a month) before presenting the paper, this research is topical and covers issues which were not examined before in academic literature. The aim of the study is to analyze major problems on which Spain has made suggestions for positive changes in the EU recently. The research was conducted with the help of such methods, as event-analysis, comparison and system approach. The article implies consistent and coherent analysis of important recent events, political and economic processes which actors were Spain and the European Union. In order to make the research comprehensive, materials of international media, ofﬁcial statements and papers of researchers from Spanish-speaking countries on associated topics were studied. The main conclusion on Spain’s participation in political and economic processes at the level of the EU is that Spain suggests different ways to strengthen economies of the Eurozone, accelerate integration in the framework of the EU, resolve migration crisis and ﬁght against terrorism in Europe. Thanks to economic growth during this year and relative stabilization of political situation after the party crisis, Spain began to participate more actively in international projects within the EU, and it is engaged in a constructive dialogue on the most urgent European problems.